ECONOMIC OBSOLESCENCE OF LAND. - Blackmore, Charles T. (The Accounting Review, 1943)
In author's opinion, land value as such is not a permanent and stable thing and, in the case of investment type properties, substantial losses are often the result of economic obsolescence in land. A reserve for normal depreciation on the improvements alone is not enough, there is need also for an adequate reserve from the earnings of the property during its estimated life of productivity to recapture not only the investment in improvements but also a part of the investment in land. Until some fifteen years ago, economic obsolescence of land was more or less an academic question. The centers of population were growing rapidly. Many people and hundreds of thousands of immigrants were taking their places on the farms. Large families were commonplace, Real estate seemed to increase in value regardless of its location. However in recent years the rate of population growth has been steadily declining. People have gradually become conscious of depreciating forces at work which were seriously affecting many of large urban centers. Not only have they experienced decentralization of population, but also a decentralization of business and industry. Technological changes-particularly, the automobile and other improved modes of transportation have brought about rapid shifts in population and, as a result, many neighborhood changes.